Roman Law for Scots Law Students - Anderson, Craig (Edinburgh University Press, 2021)
From property law to delict and unjustified enrichment, this textbook focuses on the areas of Roman law that most influenced Scots law. Students will enter practice with a greater depth of understanding of the roots of modern Scots law, helping them to feel confident in using Roman materials when tackling today's legal problems